Tree Representations: Graphics Libraries for Displaying Hierarchical Data - Mark Wilhelm (Code4Lib Journal, 2009)
Tree representations can be useful for presenting hierarchical data on the screen. In this article I’ll briefly describe building trees using the Dojo, Yahoo User Interface, Java Server Faces, and Google Web Toolkit libraries.